Incidence and Characteristic of Gastroesophageal Reflux Disease (GERD): Before and During Covid-19 Pandemic - Lubis, Masrul; Sianturi, Yolanda Anastasia (The Indonesian Society for Digestive Endoscopy, 2023)
Background: The incident numbers of gastroesophageal reflux disease (GERD) in Asia is increasing gradually from year to year. Activity restriction (lockdown) that happened during COVID-19 pandemic affects society’s eating habit and life style which are risk factors of GERD and the incidence of gastroesophageal reflux. This study was conducted to find the incidence and characteristics of GERD during COVID-19 pandemic and compared with the previous situation in patients who met the diagnostic criteria at H. Adam Malik General Hospital. Method: This research is a descriptive research study with a cross sectional design study where data were taken based on data from medical records at H. Adam Malik General Hospital in 2017–2022 with the sampling technique used is total sampling, where the research subjects were all patients diagnosed GERD that met the inclusion criteria.Results: The incidence of GERD before (2017–2019) and during the COVID-19 pandemic (2020–2022) were 21 and 37 patients respectively (there was a 76% escalation in the incidence of GERD during the COVID-19 pandemic compared to before the COVID-19 pandemic). The similar characteristics of GERD patients before and during the COVID-19 pandemic are age 40 years, work as an employee, high school graduate, and overweight body mass index (BMI).Conclusion: The incidence of GERD has increased during the COVID-19 pandemic compared to before the pandemic.